MEUNAWAH SAWAH DALAM PRAKTIK EKONOMI ISLAM (STUDI KASUS DI GAMPONG MAMPREE KECAMATAN SYAMTALIRA ARON KABUPATEN ACEH UTARA) - Fakhrurreza Fakhrurreza; Ismaulina Ismaulina; Razali Razali (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
Abstrack The practice of Meunawah Sawah is a custom that was born from the role of Islamic values ​​that entered into the cultural foundation of the Acehnese society. This practice occurs because of the limitations of paddy fields which led to the emergence of various forms of cooperative relations in the farming community in Mampree Village, Syamtalira Aron District, North Aceh Regency. The purpose of this study was to determine the practice of meunawah rice fields in Mampree Village and an overview of its Islamic economics. The research method used is a qualitative approach to the type of descriptive research. The results showed that, in Mampree Village, the owner of the paddy field surrendered the land to the cultivators to be managed, in order to get profit. The agreement was made verbally with the provision that if the seeds were provided by the owner, the results would be divided equally, but if the seeds were from the rice cultivators, then the results would be for one can (12 kg) for the owner and three cans (36 kg) for the cultivators. An overview of Islamic economics on the practice of meunawah rice fields in Mampree Village is in accordance with the practices carried out on the practice of meunawah rice fields. So it can be concluded that the practice of meunawah rice fields in Mampree Village is permitted and valid in accordance with Islamic law, because it has fulfilled the provisions in implementing cooperation in sharia economics, because it has fulfilled the pillars of Ijarah and Muzara'ah. Keywords: Practice, Meunawah, and Islamic Economy Abstrak Praktik Meunawah Sawah adalah kebiasaan yang lahir dari peranan nilai-nilai Islam yang masuk kedalam sendi budaya masyarakat Aceh. Praktik ini terjadi karena Keterbatasan lahan sawah yang menyebabkan munculnya berbagai bentuk hubungan kerjasama dalam masyarakat petani di Gampong Mampree Kecamatan Syamtalira Aron Kabupaten Aceh Utara. Tujuan penelitian ini untuk mengetahui praktik meunawah sawah di Gampong Mampree dan tinjauan ekonomi Islamnya. Metode penelitian yang gunakan adalah pendekatan kualitatif dengan jenis penelitian deskriptif. Hasil penelitian menunjukkan bahwa, Di Gampong Mampree pemilik sawah menyerahkan lahan kepada penggarap untuk dikelola, agar mendapatkan keuntungan. Perjanjiandilakukan secara lisan dengan ketentuan bila benih disediakan pemilik maka hasilnya dibagi rata, tetapijika bibit dari penggarap sawah maka bagi hasilnya satu kaleng (12Kg) bagi pemilik dan tiga kaleng (36Kg) bagi penggarap. Tinjauan ekonomi Islam terhadap praktik meunawah sawah di Gampong Mampreesudah sesuai dengan praktik yang dilakukan terhadap praktik meunawah sawah. Jadi dapat disimpulkan bahwa praktik meunawah sawah yang ada di Gampong Mampree diperbolehkan dan sah sesuai dengan hukum Islam, karena sudah memenuhi ketentuan dalam pelaksanaan kerjasama dalam ekonomi syariah, karena telah dipenuhinya rukun Ijarah dan Muzara’ah. Kata Kunci: Praktik, Meunawah, dan Ekonomi Islam.